Unravelling multilevel administration. Patterns and dynamics of administrative co-ordination in European governance. Issue 7 (8th August 2016) - Benz, Arthur; Corcaci, Andreas; Wolfgang Doser, Jan
ABSTRACT: The concept of multilevel governance adds a crucial dimension to the debate about political decision-making by conceptualizing policy co-ordination across territorial levels of government. While research on European governance has generated a differentiated analytical concept to understand the varieties of co-ordination, it has not clarified the particular role of administration, although its relevance is apparent. Research on administration in the European context has considered multilevel relations between the administrations of the European Union and its member states, but failed to cover the distinct types of interaction. In view of this state of research, we emphasize the distinct features of multilevel administration and advance the concept towards an appropriate analytical framework. By unravelling the particular role and the distinct modes of administrative interaction and patterns of co-ordination in European governance, our analytical framework should pave the way for a focused research agenda linking approaches to multilevel governance and public administration in the European and international context.